Validity of Force and Power Measures from an Integrated Rotary Encoder in a HandyGym Portable Flywheel Exercise Device - Víctor Illera-Domínguez; Xavier Font-Aragonés; Víctor Toro-Román; Samuel Díaz-Alejandre; Carla Pérez-Chirinos; Lluís Albesa-Albiol; Sara González-Millán; Bruno Fernández-Valdés (Applied Sciences)
Introduction: This study aimed to evaluate the validity of the HandyGym portable flywheel device with an integrated rotary encoder in measuring force and power during iso-inertial exercises compared to a traditional reference system. Methods: In total, 10 trained volunteers (3 women, 7 men; age 25.2 ± 3.8 years) performed half-squats with five different load configurations using the HandyGym device. Concurrent measurements were obtained from HandyGym’s rotary encoder and a criterion system (MuscleLab 6000 strain gauge and linear encoder). Five load configurations were tested, with 15 repetitions recorded per condition. The validity of the HandyGym measurements was assessed through mean bias, typical error of estimation (TEE), and Pearson correlation coefficients, with Bland–Altman plots used to analyze the agreement between the two systems. Results: The HandyGym showed high correlations with the reference system for both force (r = 0.76–0.90) and power (r = 0.60–0.94). However, systematic biases were observed, with the HandyGym consistently underestimating force and power at lower loads and overestimating power at higher loads. The TEE values indicated moderate to large errors, particularly in power measurements. Conclusion: The HandyGym provides valid force measurements with moderate bias, suitable for general monitoring. However, power measurements are less consistent, especially at higher loads, limiting the device’s utility for precise assessments. Adjustments or corrections may be necessary for accurate application in professional contexts.